Pengaruh Nomophobia Terhadap Aktivitas Fisik Mahasiswa Fakultas Kedokteran Universitas YARSI Angkatan 2019 Selama Pandemi Covid-19 dan Tinjauannya Menurut Pandangan Islam - Dahlan, Alwi; Donanti, Elita; Mahmud, Amir (Junior Medical Journal, 2024)
Background: During the current COVID-19 pandemic, many students are forced to learn with a different learning system than usual, namely the Distance Learning System. This system has caused many students to be more dependent towards their smartphones that can be associated with their everyday needs and can lead to high levels of anxiety and stress, therefore making Nomophobia one of the impacts for reduced physical activity. Methods: This study uses analytical survey method, and data was collected using a questionnaire. The population in this study are students of the Faculty of Medicine, YARSI University batch 2019. The sample selection used a simple random sampling technique. Data analysis was collected by using univariate and bivariate analysis. Results: Of the 154 respondents who are students of the Faculty of Medicine, YARSI University batch 2019, the results of the questionnaire showed that the highest results based on bivariate analysis were 38 respondents (24.7%) experiencing moderate to high nomophobia with moderate physical activity. Conclusion: There is no significant relationship between nomophobia and physical activity of students of the Faculty of Medicine, YARSI University batch 2019. In Islamic views, humans should not make possessions for their everything and always maintain health through good physical activity, and always to put their trust in Allah SWT.